Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The well known results states that:

$\lim_{n\rightarrow \infty}(1-\frac{c}{n})^n=(1/e)^c$ for any constant $c$.

I need the following limit: $\lim_{n\rightarrow \infty}(1-\frac{\ln n}{n})^n$.

Can I prove it in the following way? Let $x=\frac{n}{\ln n}$, then we get: $\lim_{n\rightarrow \infty}(1-\frac{\ln}{n})^n=\lim_{x\rightarrow \infty}(1-\frac{1}{x})^{x\ln n}=(1/e)^{\ln n}=\frac{1}{n}$.

So, $\lim_{n\rightarrow \infty}(1-\frac{\ln}{n})^n=\frac{1}{n}$.

I see that this is wrong to have an expression with $n$ after the limit. But how to show that the asymptotic behavior is $1/n$?


share|cite|improve this question
No, it is not. Finally, a limit should be a number (or infinity), how can you conclude that the limit is $1/n$? – Siminore Jun 28 '12 at 14:39
You can't have $n$ outside of the limit. Perhaps you wish to argue the function in question is asymptotically $1/n$, but that takes more work; you can't hold one part of the expression fixed, take the limit, and then take the limit of the resulting expression. For instance, you could get $$1=\lim_{x\to0}\frac{x}{x}=\lim_{x\to0}\frac{\lim_{x\to0}x}{x}=\lim_{x\to0} \frac{0}{x}=\lim_{x\to0}0=0.$$ – anon Jun 28 '12 at 14:45
Thanks! Yes, what I need is to show that the expression $(1-\frac{\ln n}{n})^n$ is asymptotically $1/n$. How I can show this? – Michael Jun 28 '12 at 14:50
If you change the nature of your question in comments, please change the question, or, if you don't have the permission, ask somebody else to change it. – Thomas Andrews Jun 28 '12 at 15:44
up vote 5 down vote accepted

According to the comments, your real aim is to prove that $x_n=n\left(1-\frac{\log n}n\right)^n$ has a non degenerate limit.

Note that $\log x_n=\log n+n\log\left(1-\frac{\log n}n\right)$ and that $\log(1-u)=-u+O(u^2)$ when $u\to0$ hence $n\log\left(1-\frac{\log n}n\right)=-\log n+O\left(\frac{(\log n)^2}n\right)$ and $\log x_n=O\left(\frac{(\log n)^2}n\right)$.

In particular, $\log x_n\to0$, hence $x_n\to1$, that is, $$ \left(1-\frac{\log n}n\right)^n\sim\frac1n. $$

Edit: In the case at hand, one knows that $\log(1-u)\leqslant-u$ for every $u$ in $[0,1)$. Hence $\log x_n\leqslant0$ and, for every $n\geqslant1$, $$ \left(1-\frac{\log n}n\right)^n\leqslant\frac1n. $$

share|cite|improve this answer
Thank you for the answer! As I asked Andre, what is the correct writing of such an asymptotic behavior? What I actually need is to show that the probability $\Pr(Event)=(1-\frac{\ln n}{n})^n$ goes to $0$ at least as fast as $1/n$. – Michael Jun 28 '12 at 15:51
See Edit. $ $ $ $ – Did Jun 28 '12 at 16:11
Thanks a lot Did!! – Michael Jun 28 '12 at 21:21

The idea you used could have worked. Exactly as you wrote, we have $$\left(1-\frac{\ln n}{n}\right)^n=\left(\left(1-\frac{1}{x}\right)^x\right)^{\ln n},$$ where $x=\frac{n}{\ln n}$.

Note that $x\to \infty$ as $n\to\infty$. Note also that $\ln n=g(x)$ for some function $g(x)$ such that $g(x)\to\infty$ as $x\to \infty$. Our limit is $$\lim_{x\to\infty}\left(1-\frac{1}{x}\right)^{g(x)}.$$ Since $\left(1-\frac{1}{x}\right)^x$ approaches $\frac{1}{e}$, and $g(x)\to\infty$, our limit is $0$.

Remark: Your impossible answer $\frac{1}{n}$ contained a large kernel of truth. When $n$ is large, $(1-1/x)^x$ is close to $1/e$, so the original expression is close to $1/n$. And of course the quantity $1/n$ approaches $0$.

Let $E(n)$ be the original expression. We can adapt your argument to show that $\lim_{n\to\infty} nE(n)=1$, which proves in a very informative way that $E(n)$ has limit $0$, by giving quite exact information about the rate of approach to $0$.

share|cite|improve this answer
Thanks! You mean in the last sentence that $E(n)$ has limit $1/n$? In general, how to correctly denote this asymptotic behavior. Since it is indeed incorrect to write that the limit when $n\rightarrow \infty$ is a function of $n$. – Michael Jun 28 '12 at 15:48
@Michael: I wrote it down in the comment above, $\lim_{n\to\infty} nE(n)=1$, or if you prefer, equivalently $\lim{n\to\infty} \frac{E(n)}{1/n}=1$. Our expression approaches $0$ like $1/n$. The most natural proof to me involves the Taylor expansion. Let $t=(\log n)/n$. Then $\log(1-t)=-t+O(t^2)$. And I had a typo at the end that I fixed, and prompted your question. the limit of $E(n)$ is $0$, of course. – André Nicolas Jun 28 '12 at 15:58
Got it! Thanks Andre! – Michael Jun 28 '12 at 16:01

Hint: consider $$ \log \left( \left( 1-\frac{\log n}{n} \right)^n \right) = n \log \left( 1-\frac{\log n}{n} \right) $$ and prove (or recall) that $$ \lim_{n \to +\infty} \frac{\log n}{n} =0. $$ Since $\log (1+\varepsilon ) \approx \varepsilon$ as $\varepsilon \to 0$, ...

share|cite|improve this answer
No: you get $$n \frac{\log \left( 1- \frac{\log n}{n} \right)}{\frac{\log n}{n}} \frac{\log n}{n} \to -\infty$$ – Siminore Jun 28 '12 at 14:56
"Since $\log (1+\varepsilon) \approx \varepsilon$ as $\varepsilon \to 0$" – Siminore Jun 28 '12 at 15:03
Fair enough. =) (I guess you can make \approx a \sim) – Pedro Tamaroff Jun 28 '12 at 15:15
The choice between $\approx$ and $\sim$ seems to depend on your culture. In Italy, we tend to use $\approx$, but also different symbols that I can't even write in TeX! – Siminore Jun 28 '12 at 16:42
OK. Good to know – Pedro Tamaroff Jun 28 '12 at 16:51

Your approach is wrong (in particular, how could your result contain $n$?).

Notice that $(1-\frac{\ln n}{n})^n=e^{n\ln(1-\frac{\ln n}{n})}$ and $\frac{\ln n}{n}\rightarrow 0$, so $n\ln(1-\frac{\ln n}{n})\sim-\ln n\rightarrow -\infty$.

Moreover $\displaystyle\lim_{n\to-\infty}e^n=0$.

Conclusion : $\displaystyle\lim_{n\to+\infty}(1-\frac{\ln n}{n})^n=0$.

share|cite|improve this answer
How does it follow that $n \log \left(1-\frac{\log n} n \right) \sim -\log n$ given that $\log n / n \to 0$? I don't think the OP knows about asymptotical behaviour, and it seems you're also using the series expansion of $\log(1-x)$ near $x=0$. – Pedro Tamaroff Jun 28 '12 at 14:56
Viewing OP's comment, I assume he knows about asymptotical behavior. – JBC Jun 28 '12 at 15:04
Yeah, it seems he does. But from the mistakes he did, I assumed he was starting with limits of this kind. – Pedro Tamaroff Jun 28 '12 at 15:12

No, it is incorrect. The answer is 0.

Since $\lim_{n\to\infty}(1-\frac{\ln n}{n})^{\frac{n}{\ln n}}=\frac{1}{e}<1$ and $\lim_{n\to\infty}\ln n=+\infty$, we have that $\lim_{n\to\infty}(1-\frac{\ln n}{n})^n=\lim_{n\to\infty}((1-\frac{\ln n}{n})^{\frac{n}{\ln n}})^{\ln n}=0$.

share|cite|improve this answer
Since you're new here, some tips: When answering it is good you be detailed, so: Why is it incorrect? Why is the answer $0$? – Pedro Tamaroff Jun 28 '12 at 14:42
On the other hand, for homework-type problems like this, maybe it is better to provide just a hint and wait for the OP to try again. – GEdgar Jun 28 '12 at 14:49
I agree with GEdgar. – Siminore Jun 28 '12 at 15:05
We have a on going debate for homework. Regardless, this didn't help the OP much, so some extra detail was necessary. – Pedro Tamaroff Jun 28 '12 at 15:07

Let $A=\lim_{n\to\infty}(1-\ln n/n)^n$. Take $\ln$ both sides,we get $lnA=\lim_{n\to\infty}n ln(1-\ln n/n)$.Now put $x=1/n$,it will give you $lnA=lim_{y\to0^+}\frac{ln(1+y\ln y)}{y}$.Using L'Hopital's Rule,you will get this limit=$-\infty$.Therefore,$\ln A=-\infty \implies A=0$.So, the required limit is $0$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.